PROBLEMATIKA GURU DALAM PEMBELAJARAN PJOK BERBASIS DARING PADA MASA PANDEMI DI MIN 8 BANJAR - Abdullah, Abdullah (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to analyze the challenges faced by Physical Education, Sports, and Health (PJOK) teachers in implementing online learning during the Covid-19 pandemic at MIN 8 Banjar. Using a qualitative approach and a descriptive method, this research explores various obstacles encountered during the online learning process, including limited access to technology, unstable internet connectivity, difficulties in supervising physical activities, and delays in assignment submissions. The findings show that teachers have made various efforts to address these issues, such as providing direct assignments to students without access to online devices and accepting late submissions. However, these challenges significantly affect the effectiveness of PJOK online learning. The study concludes that greater support in technological infrastructure and stronger collaboration among teachers, students, and parents are necessary to ensure the success of online learning, particularly for subjects that require physical activities, such as PJOK.